Penggunaan Media BIP Video Call pada Kelas Speaking - Syaifullah; Syahdan; Herlinawati (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
Based on the results of research in November 2021 concerning the use of BIP video call media in the Speaking for everyday communication course, researchers found their abilities were at the poor level. As a continuation of this research, researchers have used BIP Video Calls to improve students' Speaking skills in the Speaking for Social Media course in the form of dedication. This activity has been carried out for half a semester using several procedures; Planning, Action, Observation, and Reflection. Students who have been involved in this community service activity are Semester II students of English Education FADIKSI UNILAK who are taught in the Speaking course, especially Speaking for Social Media. In this activity there are two types of data that have been obtained; quantitative and qualitative data. Qualitative data were obtained using interview instruments. Meanwhile, quantitative data was obtained through a test instrument, namely the speaking ability test. The results that have been obtained from this study are that there is an increase in their average speaking score from 52 to 53.2. still poor category. There are two factors that influence the change in the average value; firstly the sound quality produced by BIP Vidio Call is clearer and secondly the video produces clearer visualizations. In conclusion, the use of BIP Vidio Call in the Speaking course which has been carried out in the form of research and community service has the same result, namely that it can help students expedite their communication process.